Konstruksi Etika Kristen tentang Martabat Manusia dalam Sistem Pelayanan Kesehatan Publik - Ridwan Tonny Hasiholan Pane; Pether Sobian; Frans Aliadi (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
This study is motivated by the increasing complexity of ethical challenges in public healthcare services in the modern era, characterized by rapid technological advancement, professional pressures, and shifting moral values. Within this context, Christian healthcare professionals face significant dilemmas in maintaining their faith-based ethical principles amid pragmatic service demands. This research aims to construct a Christian ethical framework on human dignity as a normative foundation for public healthcare practice. The study employs a descriptive qualitative method using a literature review approach, analyzing theological, philosophical, and social sources related to ethics, human dignity, and public service. The findings reveal that Christian ethics is rooted in the concept of Imago Dei, affirming that every human being possesses intrinsic dignity as created in the image of God. The principles of love (agape), justice, and moral responsibility serve as the core foundation for ethical healthcare practice. The implications of this study emphasize that healthcare services should not be merely technical but must also embody spiritual and humanistic values. Therefore, Christian healthcare professionals are called to act as moral agents who promote compassionate, dignified, and holistic care within the public healthcare system.